Magnesium Isoglycyrrhizinate Ameliorates Fibrosis and Disrupts TGF-β-Mediated SMAD Pathway in Activated Hepatic Stellate Cell Line LX2 - Tee, Jie Kai; Peng, Fei; Tan, Yeong Lan; Yu, Bo; Ho, Han Kiat (Frontiers in Pharmacology, 2018)
Liver fibrosis is a histological change often attributed to the activation of hepatic stellate cells (HSCs) and the excessive formation of scar tissues in the liver. Advanced stages of the disease frequently lead to cirrhosis. Magnesium isoglycyrrhizinate (MgIG) has been accepted as a hepatoprotective drug with the potential of alleviating inflammatory conditions and thus promote liver recovery from viral- or drug-induced injury. While MgIG has been empirically integrated into the clinics to treat some liver diseases, its anti-fibrotic effect and the associated mechanisms remain poorly characterized. Herein, we demonstrated that 1 mg/ml MgIG attenuated the production of αSMA and Collagen-1 in activated HSCs using TGF-β1-induced human hepatic stellate cells LX2 as the fibrotic cell model. We found that MgIG exerts an inhibitory effect on the TGF-β-SMAD signaling pathway by arresting the binding of downstream transcription factors SMAD2/3 and SMAD4. Furthermore, MgIG was shown to suppress proliferation and induce senescence of activated LX2 cells. Protein expression of p27 and enzymatic activity of senescence-associated β-galactosidase were elevated upon exposure to MgIG. In addition, we observed that exposure of activated LX2 cells to MgIG reduces TGF-β-induced apoptosis. Interestingly, a lower toxicity profile was observed when human fetal hepatocytes LO2 were exposed to the same concentration and duration of the drug, suggesting the specificity of MgIG effect towards activated hepatic stellate cells. Overall, hepatoprotective concentrations of MgIG is shown to exert a direct effect on liver fibrosis through inhibiting TGF-β-signaling, in which SMAD2/3 pathway could be one of the mechanisms responsible for the fibrotic response, thereby restoring the surviving cells towards a more quiescent phenotype. This provides critical mechanistic insights to support an otherwise empirical therapy.